Experimental Study on the Effect of Sports Games on Physical Fitness in Children Aged 4-5 Years - Yuanyuan Li (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The research aimed to evaluate the impact of sports games on the physical fitness of children aged 4-5 years through an experimental study. Data were collected from 54 children, divided into experimental and control groups, over a 12-week period with a one-hour play session per week. The SPSS 17.0 frequency analysis method was used to analyse the data and compare results betweex`n the test and reference groups to assess the effectiveness of the gameplay curriculum on children's physical development. The independent sample T-test findings indicated that the effect of sports games on children's height and weight was insignificant in both pre- and post-tests, suggesting minimal influence on body shape among 4-5-year-olds. However, the effects on physical fitness components, particularly speed, coordination, and flexibility, were significant, demonstrating considerable improvements in these areas. Post-testing results further revealed that sports games significantly enhanced upper and lower limb strength, flexibility, power, and jumping ability in the experimental group. The study, incorporating a conceptual model, presents pioneering findings for children aged 4-5 years, providing valuable insights for policymakers and organizations promoting sports games, and emphasizing the importance of integrating such activities to foster young children's engagement and physical development.